Efektivitas Proses Pengurusan Pertanahan Berbasis Online Oleh Pejabat Pembuat Akta Tanah Dikaitkan Dengan Sistem Pendaftaran Tanah - Desni Irwini Savitri; Ramlani Lina Sinaulan; Anriz Nazaruddin Halim (JOURNAL of LEGAL RESEARCH, 2022)
Today's globalized society is emerging due to advances in information and transportation technology related to complex public affairs, including the issue of online land registration at PPAT offices, an area that is emerging in parallel with the modernization process in all countries. As social and environmental changes affect the development of land management, including the government's intention to serve the community, the traditionally manual field of land management has shifted to a technology-based administrative bureaucracy. In this study, the authors used qualitative research methods and normative research types. As for the results of this study, online service applications in land registries still cannot effectively support PPAT in the execution of specific tasks related to transfer of land rights in land registration data maintenance, as online applications do not change the process, online time and cost PPAT is easier to practice effectively and efficiently, it takes longer because there are many hurdles like repetition, NIB exam and drawing are not online, so registration documents, even if they are online, have to be checked at the state office.